Conceptual design of an electroplating line in the national blender company Naliet S.A.S. (2018)
The present degree project deals with the development of a proposal for the electroplating process line at the National Blenders Company Naliet S.A.S. since the company wants to have an electroplating line that allow quality control of the chrome part. A design of experiment on the effect of time and the concentration of chromic acid with regarding the finishing of the piece in the chrome stage and thus select the most appropriate conditions for this stage as well as for the rest of stages of the conventional process. In addition, the total costs of the final proposal.